Nanoparticles: A Hope for the Treatment of Inflammation in CNS - Zhu, Feng-Dan; Hu, Yu-Jiao; Yu, Lu; Zhou, Xiao-Gang; Wu, Jian-Ming; Tang, Yong; Qin, Da-Lian; Fan, Qing-Ze; Wu, An-Guo (Frontiers in Pharmacology, 2021)
Neuroinflammation, an inflammatory response within the central nervous system (CNS), is a main hallmark of common neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Amyotrophic Lateral Sclerosis (ALS), etc. The over-activated microglia released amount of pro-inflammatory cytokines, which induces neuronal death and accelerates neurodegeneration. Therefore, inhibition of microglia over-activation and microglia-mediated neuroinflammation has been a promising strategy for the treatment of neurodegenerative diseases. Many drugs have shown promising therapeutic effects on microglia and inflammation. However, blood-brain barrier (BBB), a natural barrier preventing brain tissue from harmful plasma components, seriously hinders drug delivery to the microglial cells in CNS. As emerging and useful therapeutic tools in central neural system (CNS) related diseases, nanoparticles (NPs) have been widely applied in biomedical fields, including diagnosis, biosensing and drug delivery. Recently, many NPs are reported to be useful vehicles for carrying anti-inflammatory drugs across BBB to inhibit the over-activation of microglia and neuroinflammation. Therefore, NPs with good biodegradability and biocompatibility have the potential to be developed as an effective and minimally invasive carrier to help other drugs cross BBB or as the therapeutic agent for the treatment of neuroinflammation-mediated neurodegenerative diseases. In this review, we have summarized various nanoparticles applied in CNS, and their mechanisms and effects in the modulation of inflammation responses in neurodegenerative diseases, which provides insight and suggestion for the use of NPs in treatment of neuroinflammation-related neurodegenerative diseases.